Acoustic radiation force impulse imaging of pancreas in patients with early onset idiopathic recurrent acute pancreatitis. Issue 8 (August 2020) - Sanjeevi, Rajesh; John, Reetu Amrita; Kurien, Reuben Thomas; Dutta, Amit Kumar; Simon, Ebby George; David, Deepu; Joseph, Anjilivelil Joseph; Chowdhury, Sudipta Dhar
Abstract : Background and aims: Patients with recurrent acute pancreatitis (RAP) may progress to chronic pancreatitis (CP). A critical step in this progression is the development of fibrosis. Elastography has been used to assess degree of fibrosis by measurement of shear wave velocity (SWV). The aim of this study was to measure the stiffness of pancreas as a surrogate for pancreatic fibrosis in patients with RAP and compare it with a group of individuals without any history of pancreatic disorders. Material and methods: Using acoustic radiation force impulse (ARFI) imaging SWV was calculated in 31 patients with idiopathic RAP having disease onset ⩽30 years. A control group of 31 individuals with no history pancreatic disorder and no features of CP on endosonography was selected for comparison. ARFI imaging was done by a single radiologist who was blinded to the cases and controls Results: Mean age of patients with RAP was 24.8 (SD 9.86) years, disease duration was 3.45 (interquartile range 1–5) years, mean number of episodes 4.9 (SD 2.72). There was a significant difference in SWV between patients (1.27 ± 0.50 m/s) and controls (1.00 ± 0.17 m/s) ( P = 0.001)). There was a positive correlation between SWV and number of pain episodes ( P = 0.026) and negative correlation with BMI ( P = 0.002). Conclusion: SWV was high in patients with RAP indicating a stiff pancreas. The stiffness increases with the number of episodes of pancreatitis.